Blast effects on buildings - Cormie, David; Mays, Geoffrey; Smith, Peter (ICE Publishing, 2020)
Blast Effects on Buildings showcases the latest practical guidance on designing buildings to optimise their resilience to blast loading. Focused specifically on the design of commercial buildings, it is an indispensable guide to help engineers reduce the risks posed to building occupants and businesses from terrorist attacks and other explosions. This new third edition has been fully updated and expanded to reflect the significant developments which have occurred in the field of blast engineering. Combining coverage of design standards, codes and materials with a detailed appreciation of the needs and demands of the designer, this book offers the engineer with a single and comprehensive source of reference for all the main elements of blast engineering design in modern practice. It remains one of the only sources of published guidance on the design of vehicle security barriers, and provides an accessible, essential guide to designing structures and facades against blast loading. This title provides the reader with the latest design guidance for blast engineering and protective design, new sections on designing for groundshock and underwater explosions, details of the latest developments relating to CFD codes, multiple updated and improved worked examples for transferring theory into practice. This book is necessary reading for specialist blast engineers, structural engineers, military engineers, analysts, local authorities and government agencies.